For Some Results of Semisecond Submodules - Khalaf, Rasha I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Let â„› be a commutative ring with unity and let â„¬ be a unitary R-module. Let â„µ be a proper submodule of â„¬, â„µ is called semisecond submodule if for any râˆˆâ„›, râ‰ 0, nâˆˆZ+, either rnâ„µ=0 or rnâ„µ=râ„µ. In this work, we introduce the concept of semisecond submodule and confer numerous properties concerning with this notion. Also we study semisecond modules as a popularization of second modules, where an â„›-module â„¬ is called semisecond, if â„¬ is semisecond submodul of â„¬.